(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
In this paper, we investigate how corporate social responsibility (hereafter CSR) practices of domestic Croatian mid and large size firms differentiate them on foreign markets. Still, in order for export organizations to realize benefits offered by CSR, export organizations need to identify their main stakeholder groups and interests, and adequately design their CSR activities. This paper provides an overview of the main CSR activities of export organizations in foreign markets and analyses their stakeholder’s management as well as the quality of relationships with their primary and secondary stakeholders on foreign markets. Results of empirical research on a sample of 78 medium and large Croatian export companies show that these export organizations invest significant efforts in implementation of different CSR activities, and into relationships with their primary stakeholders. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.